2013
DOI: 10.1007/s10156-012-0489-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking on HIV infection among HIV-infected Japanese men

Abstract: We performed a cross-sectional study that included 100 HIV-infected Japanese men without hemophilia to examine the influence of smoking on HIV infection. History of smoking was obtained using a questionnaire. The percentage of current smokers was 40 % and was the highest (50 %) among men in their forties. The mean Brinkman index (BI, number of cigarettes smoked per day multiplied by years of smoking) was 450. The percentage of patients with a BI ≥600 was significantly higher in patients with an AIDS-defining e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…The odds of malnutrition after starting ART among people living with HIV who ever smoked cigarette was nearly eight-fold higher when compared to their matched counterparts. This is in line with the finding of a study conducted by Petrosillo and Cicalini in Rome [ 55 ], indicating that smoking confers different mortality risks in HIV-positive patients which can result in significantly increased mortality among HIV-positive patients who smoke than their counterparts as evidenced by several studies [ 56 60 ]. Malnutrition may be one of the risks that cause greater morbidity and mortality risk among HIV-positive patients who smoke.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The odds of malnutrition after starting ART among people living with HIV who ever smoked cigarette was nearly eight-fold higher when compared to their matched counterparts. This is in line with the finding of a study conducted by Petrosillo and Cicalini in Rome [ 55 ], indicating that smoking confers different mortality risks in HIV-positive patients which can result in significantly increased mortality among HIV-positive patients who smoke than their counterparts as evidenced by several studies [ 56 60 ]. Malnutrition may be one of the risks that cause greater morbidity and mortality risk among HIV-positive patients who smoke.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, HIV-positive patients who smoke have an increased risk of different gastrointestinal tract problems that can lower dietary intake and eventually result in malnutrition [56,61]. This is also supported by the finding from a study among HIV-infected Japanese men which identified reducing smoking as an imperative strategy in enhancing disease management efforts by reducing co-morbidities like malnutrition that increase mortality risk [60]. It could be also explained due to the association of smoking and other substance use such as alcohol, khat, cocaine, heroin marijuana etc [3638,47], which can have synergetic effect on nutritional status of people living with HIV on ART.…”
Section: Discussionmentioning
confidence: 88%
“…The observed prevalence of current smoking (29.9%) was similar to another HIV cohort from Recife, Brazil (28.9%) [7] , so far the only information available in the country. Compared to international HIV-cohorts from high [1] , [13] , [39] [41] and low [11] , [17] , [42] , [43] income settings (prevalence ranging from 40–67% and 46–47%, respectively), the prevalence found herein was considerably lower. It was also lower than the prevalence found at the SMART clinical trial (40.5%), which included 5472 HIV-infected patients from 33 countries [5] .…”
Section: Discussioncontrasting
confidence: 72%
“…Across the Asian region, the proportion of current smokers ranged from 23-62% [ 15 , 22 , 39 - 41 ] and that of former smoker from 10-20% [ 15 , 40 ]. One study specifically compared smoking among Asian populations on ART and found that compared to Thailand, the prevalence of smoking was lower in India and the Philippines, while it was higher in Vietnam, Indonesia, Hong Kong, Taiwan, Malaysia, Japan, South Korea and Singapore [ 15 ].…”
Section: Risk Factors Of Cardiovascular Diseasementioning
confidence: 99%